Effects of self‐care programs on the incidence of diabetes among adults with prediabetes: A systematic review and meta‐analysis of randomised controlled trials. Issue 9 (2nd June 2022) - Sun, Caiyun; Lei, Yang; Lin, Zheng; Li, Sha; Wang, Mi; Gu, Junyi
Abstract: Objectives: To verify the effects of self‐care programs among adults with prediabetes, to identify the preferable structure components and to summarise the core content components of self‐care programs. Design: A systematic review and meta‐analysis of randomised controlled trials. Methods: PubMed, Embase, Cochrane, CINAHL, PsycINFO, Wanfang, CNKI, Chinese Biomedical Database and Open Grey were searched for studies published from January 2002 to December, 2021. Meta‐analysis was conducted to verify the effects of self‐care programs on diabetes incidence. Subgroup analyses based on structure components were performed to contrast the effects. We made a critical analysis to generalise the core elements of content components. The study was reported according to PRISMA statement. Results: Totally, 15 studies were included in systematic review, of which 14 studies were eligible for meta‐analysis. The results of meta‐analysis showed the incidence of diabetes for prediabetic adults receiving self‐care programs was significantly lower than those who received usual care (OR 0.58; 95% CI 0.46 to 0.73). The results of subgroup analyses based on delivery mode, intervention implementer, health education brochures provided, and follow‐up duration showed statistically significant reduction in incidence compared with control group ( p < .05). However, the differences of these pair‐wise comparisons (face‐to‐face or remote, individual or interdisciplinary team, with or without brochures provided, ≤1 year or >1 year) were not statistically significant ( p > .05). Three core content elements were generalised: cognitive education, behaviour guidance and psychological support. Conclusions: Self‐care programs can effectively delay the progression of prediabetes to diabetes. Regardless of the diversified structure components, self‐care programs can achieve better effects on the diabetes incidence than usual care, while the optimal structure components still remain unknown. Cognitive education, behaviour guidance and psychological support are core elements for these programs. Relevance to clinical practice: More clinical trials with rigorous study design are needed to provide further evidence.